A New Taxonomy of Monetary Regimes - Bhundia, Ashok (IMF Working Papers; Working Paper, 2004)
This paper proposes a new taxonomy of monetary regimes defined by the choice and clarity of the nominal anchor. The regimes are as follows: (i) monetary nonautonomy, (ii) weak anchor, (iii) money anchor, (iv) exchange rate peg, (v) full-fledged inflation targeting, (vi) implicit price stability anchor, and (vii) inflation targeting lite. This taxonomy captures the commitment-discretion tradeoffs that lie at the heart of choosing a monetary regime. During the last 15 years the world has moved toward monetary regimes with less discretion. Empirical analysis suggests that country regime choices reflect the level of financial and economic development and recent inflation history.